Embedding of Besov Spaces and the Volterra Integral Operator - Dan Qu; Xiangling Zhu; Ruishen Qian (Journal of Mathematics)
The boundedness and compactness of the inclusion mapping from Besov spaces to tent spaces are studied in this paper. Meanwhile, the boundedness, compactness, and essential norm of the Volterra integral operator Tg from Besov spaces to a class of general function spaces are also investigated.